2019
DOI: 10.1007/s40615-019-00606-8
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious Racism Stress and Disease Activity: the Black Women’s Experiences Living with Lupus (BeWELL) Study

Abstract: Background: Indirect or vicarious exposure to racism (e.g., hearing about or observing acts of racism or discrimination) is a salient source of stress for African Americans. Emerging research suggests that these "secondhand" experiences of racism may contribute to racial health inequities through stress-mediated pathways. Systemic lupus erythematosus (SLE) is an inflammatory autoimmune disease that disproportionately impacts African American women and is characterized by racial disparities in severity. Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…Previous research shows that both short-term acute stress experiences as well as prolonged stress, particularly due to social identity threat, has lasting physiologic impacts [ 38 , 39 ]. Further, even when not the target of direct racial discrimination or harassment, vicarious racial discrimination has been associated with poorer mental and physical health [ 40 ], especially among those with higher levels of racial group identification [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that both short-term acute stress experiences as well as prolonged stress, particularly due to social identity threat, has lasting physiologic impacts [ 38 , 39 ]. Further, even when not the target of direct racial discrimination or harassment, vicarious racial discrimination has been associated with poorer mental and physical health [ 40 ], especially among those with higher levels of racial group identification [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vicarious Racism Stress. To assess distress in response to the indirect exposure to racism during COVID-19, four items from past research (Martz et al, 2019) were administered at Wave 3 -"hearing people being the victims of racism in the news," "hearing about family members or friends who experienced racism," "seeing other people in public being treated unfairly because of their race," and "seeing racism depicted in movies or television shows. "…”
Section: Methodsmentioning
confidence: 99%
“…In the unfolding process of COVID-19, the murder of George Floyd on May 25 th , 2020, along with other high-profile cases covered by media during quarantine, further exacerbated collective wounds of American society, especially among Black communities (Silver et al, 2020). To this end, we assessed the stress experienced by parents from vicarious racism, or secondary exposure to racial discrimination (Martz et al, 2019). As emerging studies demonstrated evidence of negative health consequences from indirect exposure to racism events (Bor et al, 2018;Martz et al, 2019), we hypothesized vicarious racism stress as a risk factor associated with maladjusted trajectories.…”
Section: Protective and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater racial discrimination correlated with both higher disease activity and organ damage after adjusting for socioeconomic and health-related factors. The same group of investigators further examined the relationship between vicarious racism and disease activity in the GOAL sample of African-American women with SLE [25]. Vicarious racism is a ‘secondhand’ type of exposure to racism (e.g., hearing about or observing acts of racism or discrimination) that causes psychosocial stress and may contribute to health disparities.…”
Section: The Centers For Disease Control and Prevention Population-bamentioning
confidence: 99%